OPTIMASI PENEMPATAN KAPASITOR PADA PENYULANG KOTA CALANG DENGAN METODE MODIFIED BACKWARD-FORWARD SWEEP - Zakwansyah; Ira Devi Sara; Rakhmad Syafutra Lubis; Budi Amri (J-Innovation, 2018)
This study presents capacitor installation to reduced losses line, moreover improve voltage profile and power factor improvement. Capacitor optimization installed using modified backward forward sweep with the result that installation point and capacity appropriate. The modified backward-forward sweep have been tested on 15 BUS Kota Calang 20 kV feeder distribution, Aceh Barat. Initial simulation of feeder was result 0,85 kW line losses with 19,9753 minimum voltage. After capacitor installation on BUS 4, BUS 6, BUS 8 and BUS 13, the minimum losses line is reduced to 0,66 kW.